Love Thy Extra-Terrestrial Neighbour: Charity and Compassion in Luc Besson's Space Operas The Fifth Element (1997) and Valerian and the City of a Thousand Planets (2017) - Magerstädt, Sylvie (Religions, 2018)
The role of romantic love in cinema-and its redeeming aspects-has been extensively explored in film studies and beyond. However, non-romantic aspects of love, especially love for the neighbour, have not yet received as much attention. This is particularly true when looking at mainstream science fiction cinema. This is surprising as the interstellar outlook of many of these films and consequently the interaction with a whole range of new neighbours' raises an entirely new set of challenges. In this article, the author explores these issues with regard to Luc Besson's science fiction spectacles The Fifth Element (1997) and Valerian and the City of a Thousand Planets (2017). Both films have divided fans and critics and it is indeed easy to dismiss them as mere spectacle with little depth or message, as many reviewers have done. Yet, as this article demonstrates, beneath their shiny, colourful surface, both films make a distinct contribution to the theme of neighbourly love. What is more, Besson's films often seem to develop a close link between more common notions of romantic love and agapic forms of love and thus offer a perspective of exploring our relationship to the alien as our neighbour.